Theoretical investigation of the impact of zinc ion in the center of trimer porphyrins on the electrical and thermoelectric properties - Hassan, Ghofran Zamel; Noori, Mohammed Deia (Edelweiss Applied Science and Technology, 2025)
Thermoelectrics as a way to use waste heat is essential in many electronic applications. In this work, the effect of the appearance of zinc ions in the center of trimer porphyrins on the electronic and thermoelectric properties of zinc porphyrin trimer molecular junctions was investigated theoretically using a combination of density functional theory (DFT) methods. Our results show that all electronic and thermoelectric properties have been affected by the appearance of zinc ions in the center of porphyrin trimer units. However, the findings indicate that the presence of a zinc metal ion in the center of the porphyrin trimers with one, two, or three zinc ions significantly affects their electronic and thermal conductance, particularly in the vicinity of the Fermi energy.